Using newspapers to improve narrative writing among secondary school students / Saibah binti Awang Ahmad - Awang Ahmad, Saibah (2012)
Due to limited exposure and usage of the English language, many secondary school students in rural areas have difficulty in writing a narrative essay. The main reason given is lack of vocabulary. Hence, this research is to find out the student’s performance in narrative essay writing after an intervention in vocabulary acquisition using The Star newspaper as an alternative teaching and learning material. Activities using the newspaper are carried out for six weeks, at a frequency of 2 to 3 times a week. The methods applied in this study are pretest, post-test and interviews. The pre-test and post-test design is used to gather the quantitative data and interviews with the teacher and students are used to obtain qualitative data. The tests comprise free writing where the participants write a story that ends with the ‘line’ given. The participants of this research are 30 Form Four students from a rural secondary school in the district of Gombak, Selangor. After the administration of the pre-test, the students carry out 5 vocabulary worksheets and 3 writing worksheets based on selected articles from The Star. During the treatment, their behaviors or attitudes in responding to the questions asked and also their reactions to the teacher’s instruction were recorded as field notes. Upon completion of the 8 worksheets, a post-test was administered. The difference between the pre and post-test scores for each student was then analyzed. Out of the 30 participants, 9 students (30%) were selected to be interviewed. The teacher was also interviewed. The result indicated that the activities using the newspaper did help the students to acquire more vocabulary, however, the newly acquired vocabulary helped improve the narrative writing of good and average students only. This is because these students know how to use the words learned correctly in elaborating their ideas. Whereas, for the weak students, they need more time to learn how to apply the words in their essay.